Rosai Dorfman Disease - Chowdhury, Md Faizul Islam; Khandaker, MA Kashem; Zaid, Hossain M; Khatun, Hazera; Hossain, Md Murad; Karim, Enamul (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mr. Shahinoor an 18 year old male got himself admitted at DMCH in July,2007 with the complaints of bilateral neck swelling and fever for 1 month. The enlarged lymph nodes were clustered in cervical regions involving both anterior and posterior chains and largest one measuring 5 cmÃ2.5 cm.He was otherwise healthy on examination. Full blood count showed neutrophil leukocytosis and raised ESR.Sputum for AFB was found negative and xray chest was normal. FNA of lymph node showed non specific lymphadenitis with reactive hyperplasis. Lymph node biopsy was done and histopathology revealed Rosai Dorfman Disease, a very rare yet fascinating disorder also called Sinus Histiocytosis with Massive Lymphadenopathy.It is a benign proliferative disorder of the histiocytes. He was not given any tretament and is under follow up. Â  DOI = 10.3329/jom.v8i1.1376 J MEDICINE 2007; 8 : 28-31